Runx1 Isoforms Show Differential Expression Patterns During Hematopoietic Development But Have Similar Functional Effects in Adult Hematopoietic Stem Cells - Challen, Grant A. (2010)
OBJECTIVE: RUNX1/AML1 is an essential regulator of hematopoiesis and has multiple isoforms arising from differential splicing and utilization of two promoters. We hypothesized that the rare Runx1c isoform has a distinct role in hematopoietic stem cells (HSCs). METHODS: We have characterized the expression pattern of Runx1c in mouse embryos and human embryonic stem cell (hESC)-derived embryoid bodies using in situ hybridization, and expression levels in mouse and human HSCs by real-time PCR. We then determined the functional effects of Runx1c using enforced retroviral over-expression in mouse HSCs. RESULTS: We observed differential expression profiles of RUNX1 isoforms during hematopoietic differentiation of hESCs. The RUNX1a and RUNX1b isoforms were expressed consistently throughout hematopoietic differentiation whereas the RUNX1c isoform was only expressed at the time of emergence of definitive HSCs. RUNX1c was also expressed in the AGM region of E10.5–11.5 mouse embryos, the region where definitive HSCs arise. These observations suggested that the RUNX1c isoform may be important for the specification or function of definitive HSCs. However, using retroviral over-expression to study the effect of RUNX1 isoforms on HSCs in a gain-of-function system, no discernable functional difference could be identified between RUNX1 isoforms in mouse HSCs. Over-expression of both RUNX1b and RUNX1c induced quiescence in mouse HSCs in vitro and in vivo. CONCLUSIONS: Although the divergent expression profiles of Runx1 isoforms during development suggest specific roles for these proteins at different stages of HSC maturation, we could not detect an important functional distinction in adult mouse HSCs using our assay systems.